2016
DOI: 10.3892/etm.2016.3179
|View full text |Cite
|
Sign up to set email alerts
|

Allicin inhibits oxidative stress-induced mitochondrial dysfunction and apoptosis by promoting PI3K/AKT and CREB/ERK signaling in osteoblast cells

Abstract: Abstract.Osteoporosis is a disease of the skeleton that is characterized by the loss of bone mass and degeneration of bone microstructure, resulting in an increased risk of fracture. Oxidative stress, which is known to promote oxidative damage to mitochondrial function and also cell apoptosis, has been recently indicated to be implicated in osteoporosis. However, there are few agents that counteract oxidative stress in osteoporosis. In the present study, the protective effects of allicin against the oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 47 publications
0
34
0
Order By: Relevance
“…Mechanistically, PDGF-BB upregulated periostin expression via inducing the phosphorylation of PDGFR-β, PI3K, AKT, and CREB. CREB is essential for enhanced osteogenic formation, which is modulated by PI3K/AKT signaling (55,56), but the downstream target of CREB in PDCs has not been well characterized. We showed that PDGF-BB could induce direct binding of pCREB to periostin promoter in ChIP assay.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, PDGF-BB upregulated periostin expression via inducing the phosphorylation of PDGFR-β, PI3K, AKT, and CREB. CREB is essential for enhanced osteogenic formation, which is modulated by PI3K/AKT signaling (55,56), but the downstream target of CREB in PDCs has not been well characterized. We showed that PDGF-BB could induce direct binding of pCREB to periostin promoter in ChIP assay.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress, a biochemical imbalance between endogenous antioxidant and oxidant formation, has been thought to play an essential role in the pathogenesis of various diseases [26]. Furthermore, mitochondria, key organelles in eukaryotic cells, are essential for cellular energy Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The high energy consumption required for the rapid growth of marine fish larvae also makes them vulnerable to oxidative stress ( Liu et al, 2015 ). Early studies have shown that allicin can protect osteoblasts from H 2 O 2 -induced oxidative stress ( Ding et al, 2016 ), and allicin can scavenge oxygen free radicals and also affect the antioxidant capacity of animals ( Chung, 2006 ). Purportedly, allicin protects cells against oxidative stress by inducing the production of antioxidant enzymes ( El-Sheakh et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%